Respuesta :

Step-by-step explanation:

I think the other answer tries to answer here a different question.

for this actual question here :

5(3x + 9) - 2x = 15x - 2(x - 5)

15x + 45 - 2x = 15x - 2x + 10

45 = 10

I think there are some pieces missing in the description.

with what you have given me here, all terms with x cancel each other out. none remains. only some constant numbers remain, and with 45=10 this gives a false statement, so there are no solutions for this.

The solution of the equation 5(3x + 9) – 2x = 15x – 2(x – 5) for x is 0 = -40(no solution)

How to solve equation for unknown

Given:

5(3x + 9) – 2x = 15x – 2(x – 5)

15x + 45 - 2x = 15x - 2x + 5

  • collect like terms

15x - 2x - 15x + 2x = 5 - 45

  • simplify

0 = - 40

The equation 5(3x + 9) – 2x = 15x – 2(x – 5) has no solution

Learn more about equation:

https://brainly.com/question/16863577

ACCESS MORE